Development of Physics E-Modules based on Ethical Dilemma STEAM on Renewable Energy Material - Mahmudah Mahmudah; Hadi Nasbey; Upik Pratiwi (Journal of Advances in Physics Education, 2025)
The aim of this development research is to produce a physics e-module based on the Ethical Dilemma STEAM on Renewable Energy material. The model development used in this research is 3D model which is a modification of the Thiagarajan 4D model. This model consists of three development stages, namely Define, Design, and Develop. The research results obtained a learning media product in the form of an electronic module in Canva Website format which consists of three learning activities. This module can be used as an independent learning media that can be used by high school students to enrich their understanding of physics learning on the topic of renewable energy.